Scottish council tax: Ripe for reform - Stuart Adam; David Phillips; Sam Ray-Chaudhuri (Institute for Fiscal Studies (IFS), 2025)
Council tax is levied on the occupiers of residential property to help fund the provision of local services. Individual Scottish councils set the tax rates for their area, but it is the Scottish Government that determines the tax base to which the tax rates apply. With properties still assigned to tax bands based on an assessment of how much they were (or would have been) worth in April 1991, this tax base is now over a third of a century out of date. The tax rates are a lower share of property value for high-value properties: the tax is regressive with respect to property value. And a range of discounts and exemptions distort the usage of residential property, in particular contributing to both the overcrowding and the underoccupation of property. Revaluation and reform of council tax could improve the fairness and efficiency of Scotland's tax system, especially if combined with reforms to Scotland's other property taxes. With a process of stakeholder engagement on reform of council tax set to take place this year, it is an opportune time to consider the options and potential impacts on different types of Scottish households. This chapter of our Budget Report sets out the case for revaluing and reforming Scotland's council tax, analyses the potential impact of two example reforms on different types of households, and discusses a number of practical considerations for a successful reform, such as transitional arrangements and legislation for regular future revaluation.
Keywords: 330; Taxes and benefits; Devolved government finances; Scotland; Property taxes; Tax